Innovation and growth: Evidence from Latin American countries - Luis Alfredo Avila-Lopez; Chaofeng Lyu; Santos López Leyva (Journal of Applied Economics, 2019)
This paper aims to analyze the relationship between innovation and per capita economic growth over the long-run for 12 Latin American countries for the period 1996-2015. This study uses six different indicators of innovation. Using Granger causality test, the study finds the presence of unidirectional and bidirectional causalities between innovation and per capita economic growth. These results vary. Latin America is a diverse region, depending upon the types of innovation indicators that we use in the empirical investigation process. It is important to note that all these innovation indicators are considerably linked with per capita economic growth.
Keywords: 330; development; economic growth; Innovation; Latin America